Incongruity between World Play and Purpose: Disaster-prone Human and Their Alienation in Chekhov’s ‘Enemies’ and ‘A Swan-Song’ - Ghimire, Rishiram (Bon Voyage, 2025)
This article analyzes Anton Chekhov’s short story “Enemies” and a one-act play “A Swan-Song” how life is absurd in the modern world and the characters Aboguin and Svetlovidov respectively go through deceptive maneuver. The deceptive maneuver, in the inconsistent world, denotes the sense of insecurity and loneliness of a person and the person feels being threatened by his/her situation and people around him/her. Modern people, though living with their kith and kin, feel lonely and do not find themselves safe and attended, and their trust on their friends and relatives shatters anytime unexpectedly. The feeling of being deserted has infiltrated this world now and the people suffer from personal loneliness and social alienation. Aboguin and Svetlovidov, though they are true to their love and the demand of the audience respectively, undergo abandonment from their trustees, wife and audience for whom they exert any means they have. While analyzing these two stories, the researcher uses the insight of Albert Camus’s absurdism that portrays the apprehension of modern people. This article concentrates on ‘why Chekhov’s characters undergo betrayal and indifference though their veracity to their duty and responsibility suffices.’